Towards a Connected Society: Implementation of the 5G Network and its Impact on Social and Economic Interaction in Panimbang District - Pirdaus, Dede Irman; Saputra, Jumadil (Research Collaboration Community (RCC), 2024)
In the era of digital transformation that continues to develop, the implementation of the 5G network is the main pillar for increasing connectivity and accelerating economic growth. Panimbang District, as an integral part of the dynamics of globalization, is positioned to experience a substantial impact from these technological advances. This article reviews in detail the key characteristics of 5G networks, such as high speed, low latency, and large capacity, and investigates their impact on social interactions and the economy in Panimbang District. Apart from that, it also discusses practical steps in implementation, including infrastructure planning, frequency spectrum allocation, and innovative technologies such as beamforming. By bringing Panimbang District into an era of high-level connectivity, it is hoped that there will be a deep transformation in the way people interact and manage the local economy.